2018
DOI: 10.4103/abr.abr_124_17
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Alters Sodium Excretion and Renal Clearance in Rats: Gender and Drug Dose Related

Abstract: Background:Nephrotoxicity is one of the side effects of cisplatin (CP) therapy which is gender related. CP disturbs renal function through glomerular filtration rate and electrolytes transport disturbances. This study was designed to compare some markers related to renal function in two protocols of CP treatment in rats.Materials and Methods:Male and female rats were subjected to receive single (treat 1; 7.5 mg/kg) and continues doses (treat 2; 3 mg/kg/day for 5 days) of CP, and the measurements were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The levels of urea and creatinine can also be influenced by gender in humans (Tzamaloukas et al, 1998). A study on the exposure of rats to cisplatin demonstrated that females had higher levels of urea and creatinine than males (Jilanchi et al, 2018). Like other studies, higher levels of AST, ALT, and urea were observed in females exposed to GBH than those in males in this study; however, no gender-based distinctions were observed in the histological parameters (structural damage and NOR numbers).…”
Section: Discussionsupporting
confidence: 46%
“…The levels of urea and creatinine can also be influenced by gender in humans (Tzamaloukas et al, 1998). A study on the exposure of rats to cisplatin demonstrated that females had higher levels of urea and creatinine than males (Jilanchi et al, 2018). Like other studies, higher levels of AST, ALT, and urea were observed in females exposed to GBH than those in males in this study; however, no gender-based distinctions were observed in the histological parameters (structural damage and NOR numbers).…”
Section: Discussionsupporting
confidence: 46%
“…Several studies indicate that cisplatin accumulation in kidneys results in inflammation, increases lipid peroxidation, and reduces the level of antioxidant, mitochondrial dysfunction, along with deoxyribonucleic acid (DNA) adduct formation and activation of apoptotic pathways. [ 9 ] Moreover, the accumulation of cisplatin is found to be more than five times in kidney as compared to the blood. As a result of which, the concentration of cisplatin in kidney is very high (resulting in toxicity) as compared to the concentration in the blood which is generally nontoxic.…”
Section: Introductionmentioning
confidence: 99%